Prarancangan Pabrik Propilen Glikol Dari Gliserol Dengan Desain Alat Utama Kolom Distilasi (D-102) - Balqis, Mutiara Sri; Fadli, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Propylene glycol or 1,2-propanediol is an organic compound that has low toxicity so it is used as a raw material in food products, cosmetics, and medicines. Propylene glycol is used as a solvent and preservative, moisturizer, medicinal formula and viscosity stabilizer in paints.The purity of propylene glycol that meets USP (United States Pharmacopeia) standards is >99.5% The need for propylene glycol increases over time. The increase in demand for propylene glycol is projected at 5% per year based on data from the BPS (Badan Pusat Statistika) for the last 6 years. However, until now there has not been a single Indonesian company that produces propylene glycol, so domestic needs still rely on imports. The increasing need for imports will reduce the source of foreign exchange for the country. Therefore, the construction of a propylene glycol plant is indispensable. The purpose of this study is to get an overview of calculations regarding propylene glycol factories in Indonesia with the main design is a distillation column (D-102) which serves to increase the purity of propylene glycol. The type of distillation column used is the tray column with the diameter of coloumn is 21,50 inch and the height of coloumn is 425,19 inch. The operating conditions in the distillation column are temperature of 460oK and an operating pressure of 1 atm. Plant economic analysis is carried out to determine the feasibility of the factory to be built. Based on the results of the economic feasibility analysis of the factory, the propylene glycol plant is feasible to build with a 1,39-year POT, 42% BEP, 22.79% IRR, and 57% ROI.Keywords: propylene glycol, distillation, economic analysis, imports